IMPLEMENTASI PEMBENTUKAN SIKAP DISIPLIN SISWA MELALUI BUDAYA RELIGIUS di SMP PLUS FITYANI PUJON - Choiriyah Anggraini; Chalimatus Sa’dijah; Ibnu Jazari (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
The importance of a disciplinary attitude that must be owned by everyone, because with the attitude of discipline all work will be completed in a timely manner. Through the religioups culture that is applied by the school, it becomes one of the school's efforts to implement a disciplined attitude, which is expected to be able to make students able to be disciplined in all matters, both worship and others. The use of a qualitative approach makes the method of observation, interviews and documentation a technique of data collection, which is then analyzed and checked the validity of the data so as to produce a valid result, namely in the form of religious cultural forms in forming student discipline attitudes, among others: morning apples (pray together), congregational prayers, Al-Qur'an tadarus, recitation or almsgiving, smiling sapa salim movements, and filling in BLP honesty books (building learning power) and supported by several strategies, so that religious cultural activities are carried out to form a disciplined attitude to students in Pujon Fityani Middle School. Indeed, with the existence of religious culture habituation in Pujon Fityani Middle School becomes one way for students to learn to form a disciplined and accustomed attitude in doing it in school and in the surrounding environment.